1999
DOI: 10.1007/s000110050515
|View full text |Cite
|
Sign up to set email alerts
|

Chemoattractant-induced release of elastase by tumor necrosis factor-primed human neutrophils: Auto-regulation by endogenous adenosine

Abstract: Endogenous adenosine down-regulates the cell secretory response and is instrumental in uncovering the susceptibility of azurophilic granule exocytosis to control by inhibitors of phosphodiesterase type IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…The effects of ADA, and by implication those of endogenous adenosine, on isolated neutrophil activities such as superoxide production, adhesion to vascular endothelium, degranulation and synthesis of cAMP are well-characterised [2,8,11], and have largely been confirmed in the present study. However, we are unaware of integrated studies, such as the current study, undertaken to compare the time courses of alterations in IP 3 , cytosolic Ca 2+ and cAMP concentrations in FMLP-activated neutrophils in the presence and absence of The results of 12 experiments are expressed as the mean percentages ± s.e.m.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The effects of ADA, and by implication those of endogenous adenosine, on isolated neutrophil activities such as superoxide production, adhesion to vascular endothelium, degranulation and synthesis of cAMP are well-characterised [2,8,11], and have largely been confirmed in the present study. However, we are unaware of integrated studies, such as the current study, undertaken to compare the time courses of alterations in IP 3 , cytosolic Ca 2+ and cAMP concentrations in FMLP-activated neutrophils in the presence and absence of The results of 12 experiments are expressed as the mean percentages ± s.e.m.…”
Section: Discussionsupporting
confidence: 66%
“…At sites of inflammation the autocrine anti-inflammatory actions of neutrophil-derived adenosine may be potentiated by release of the nucleoside from other types of inflammatory cells such as endothelial cells [3,4] and platelets [5], as well as from bystander tissue cells [6,7]. Neutrophil functions suppressed by adenosine include adhesion to vascular endothelium [2], actin polymerisation [8], superoxide production [8,9] and granule enzyme release [10,11], as well as activity of phospholipases A 2 and D, and 5¢-lipoxygenase [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Nimesulide, like some classical NSAIDs exhibits a considerable degree of anti-infl ammatory activity as a consequence of various inhibitory effects on polymorphonuclear neutrophil leucocytes (PMNs) (Dallegri et al, 1990(Dallegri et al, , 1992a(Dallegri et al, , 1992bOttonello et al, 1992Ottonello et al, , 1993Ottonello et al, , 1995Ottonello et al, , 1999Capecchi et al, 1993;Verhoeven et al, 1993;Bevilacqua et al, 1994;Dapino et al, 1994;Tool and Verhoeven, 1995;Bennett and Villa, 2000;Bennett, 2001;Mouithys-Mickalad et al, 2000;Nakatani et al, 2001;Gomez-Gaviro et al, 2002;Bravo-Cuellar et al, 2003;Kimura et al, 2003;Rainsford et al, 2005). These effects are, in some cases, relatively potent compared with the activities of other NSAIDs, and occur within the drug concentrations in plasma or synovial fl uids encountered during therapy with the drug Bennett and Villa, 2000;Bennett, 2001).…”
Section: Cox-2 and Anti-infl Ammatory Activitymentioning
confidence: 98%
“…sFasL may be a direct chemoattractant for neutrophils. In vitro studies involving Boyden chamber migration assays suggested that the neutrophil response could be triggered by the establishment of sFasL chemoattractant gradient (Ottonello et al, 1999). Therefore, membrane-bound FasL and sFasL produced from these inflammatory cells may function as chemokines for neutrophils in the early stage of postreperfusion, and in this study, anti-FasL antibody neutralized this chemotactic activity, leading to a 41% decrease in neutrophil infiltration.…”
Section: Discussionmentioning
confidence: 54%
“…This response was observed in a variety of cell lines and tissues, namely, islets (Allison et al, 1997;Kang et al, 1997b), myoblasts (Kang et al, 1997a), and tumor cells (Arai et al, 1997;Miwa et al, 1998;Seino et al, 1997). Furthermore, a soluble type of FasL (sFasL) was a potent chemoattractant for human neutrophils (Ottonello et al, 1999 (Desbarats et al, 1998). It is known that neutrophils, macrophages, and T cells express FasL (Kiener et al, 1997;Liles et al, 1996;Nagata, 1994).…”
mentioning
confidence: 99%